EXPLORING STUDENTS’ PERCEPTION OF E-LEARNING IN STUDYING ENGLISH DURING COVID-19 PANDEMIC: A Study at the Eighth Grade Students of SMP Islam Athirah 1 Makassar - Syam, Lisa Azaria Sukma; Hamid, Radiah; Jumiaty, Andi Asri (FKIP Unismuh Makassar, 2021)
This research aims to know the students’ perception of e-learning in studying English and to find out the students’ problems in e-learning during the Covid-19 pandemic at the Eighth Grade of SMP Islam Athirah 1 Makassar. The design of this research is Descriptive Quantitative. The population of the research was the Eighth Grade students of SMP Islam Athirah 1 Makassar which consist of 30 samples. The technique was Random Sampling Technique and the data were collected by the questionnaire. The researcher used Likert Scale and descriptive analysis to analyze the data. The result of this study shows that the students perception of e-learning in studying English during Covid-19 pandemic have positive respond, most of students was agree with the benefits of e-learning. While the students’ problems faced was the level of concentration and seriousness of their learning decreased during online learning. The internet access is not stable and device facilities, such as smartphone and laptop do not support in accessing e-learning. The students were also difficult to understand the material provided by the teacher and have difficulty doing individual assignments and group assignments that have to work on together by online. The last problems were the students easily experience stress during e-learning. Based on the result, it could be concluded that students enjoyed the benefits of e-learning, but the sudden adoption of online learning and lack of preparation, raises several problems.